2015
DOI: 10.1071/sh14210
|View full text |Cite
|
Sign up to set email alerts
|

Pap smear rates among Australian community-attached lesbian and bisexual women: some good news but disparities persist

Abstract: Abstract:Background: Research in the US and UK shows lesbian women are less likely than their heterosexual peers to attend for routine Pap smear tests. This study examined Pap smear test rates among community-attached lesbian, bisexual and queer (LBQ) women in New South Wales, to investigate if rates had changed between 2002 and 2012, compare rates to the general NSW population and identify predictive factors for Pap smear test attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
4
3
0
Order By: Relevance
“…As such, SC related to sexual minority status may contribute specifically to sexual, rather than general health care underutilization. This is consistent with the finding that for many SMW, sexual and reproductive health care services are not included as a component of routine health care (Douglas, Deacon, & Mooney-Somers, 2014). It remains unclear what prevents SMW from timely accessing BCCS when they otherwise keep up with routine care, but our results suggest SC as a possible factor.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As such, SC related to sexual minority status may contribute specifically to sexual, rather than general health care underutilization. This is consistent with the finding that for many SMW, sexual and reproductive health care services are not included as a component of routine health care (Douglas, Deacon, & Mooney-Somers, 2014). It remains unclear what prevents SMW from timely accessing BCCS when they otherwise keep up with routine care, but our results suggest SC as a possible factor.…”
Section: Discussionsupporting
confidence: 91%
“…As such, SC related to sexual minority status may contribute specifically to sexual, rather than general health care underutilization. This is consistent with the finding that for many SMW, sexual and reproductive health care services are not included as a component of routine health care (Douglas, Deacon, & Mooney-Somers, 2014)…”
Section: Stigma Consciousness (Sc)supporting
confidence: 91%
“…To the best of our knowledge, this is the first study to examine the cervical cancer screening and HPV vaccination rates among SMW in Korea, especially with respect to the sex of their sexual partners. In this study, the rate of cervical cancer screening among Korean SMW in the last two years was lower than that of the general population or that of SMW in western countries, which was reported to be between 43% and 69% [7,12,24]. Our findings are consistent with those of previous reports, which showed that the screening rate of SMW was lower than that of the general population [5,25].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, nearly two of five GBQ men in 2019 reported weekly binge drinking (38.2%), nearly one-quarter at least monthly (24.5%), and a slightly smaller proportion (22.4%) binge drinking once or twice in the previous six months (Broady et al, 2019). Compared to national guidelines for cancer screening, community health surveys reported that 34% of LBQ women were overdue to attend cervical cancer screening; that is, they were last screened more than three years ago, never had engaged with screening or were not sure when they last engaged with screening (Douglas et al, 2015;Mooney-Somers et al, 2018).…”
Section: What Does This Paper Add To This Topic?mentioning
confidence: 99%